Social aspects associated with genetic engineering in agriculture - Wieczorek, Ania (Henry Stewart Talks, 2013)
Food safety of genetically engineered (GE) crops for human and animal consumption, Environmental safety of GE crops the environment, Regulation of GE crops, The need for GE technology, Ethical and moral issues of using GE, Foods created through GE (natural or not?), Coexistence/ food labeling, GE crops in developing countries
Updated at 2014/07/01